Jimmy’s Hall, Irish Cinema and the Telling of History - Ruth Barton (Review of Irish Studies in Europe, 2016)
Ken Loach’s Jimmy’s Hall reorganises heritage principles to produce a narrative that allows for utopian moments to appear within an otherwise conventionally tragic retelling of Irish history. In certain ways, it also reflects a very specific left wing British view of Irish history (as a textbook case of the terrible consequences of the imperial endeavour); it offers certain broad stereotypes of Irish identity (particularly of Irish gender identity), and it lacks an ear for local speech inflections that are grating for anyone familiar with the time and place of its setting. However, at its best, and particularly through its use of music and its invocation of the dancehall as a utopian space, it captures that sense of hope, misplaced as it turned out to be, that emerges in other people’s memories and interpretations of the events of the Jimmy Gralton story.